Performance degradation and recovery characteristics during gas purging in a proton exchange membrane fuel cell with a dead-ended anode - Chen, Ben (2020)
Proton exchange membrane fuel cells operated in the dead-ended anode mode can improve the utilization of hydrogen and simplify the fuel cell system. Gas purging was an effective way to remove the excess water to avoid water flooding and performance degradation in PEMFC. Effective back diffusion of water from the cathode to the anode was critical for performance recovery after gas purging. The purging operation was the process of water rebalancing in the electrode. The water back diffusion rate across the membrane was mainly related to temperature, pressure and current density. The performance degradation and recovery characteristics during the purging process in a proton exchange membrane fuel cell with a dead-ended anode were investigated under various operating conditions in this paper. Performance decreased rapidly during the duration of purging, after which it increased immediately at first and then gradually reached its original level a few seconds after gas purging. Nevertheless, performance would eventually stabilize before the next purging operation was begun.